Arche as energeia : a study of metaphysics Theta - Su, Jun (Trinity College (Dublin, Ireland). Philosophy Department, 2017)
The central thesis and its significance: My central thesis in this dissertation is this: Aristotle's Metaphysics Theta is an argumentative unity, both in itself and within the overall project of the Metaphysics. What unifies Theta and links it to the rest of the Metaphysics is the project of searching for the arche of ousiai. This dissertation will defend the above thesis by focusing on some key issues surrounding the argumentative structure of Theta. Through offering solutions to these puzzles, a clearer and more precise picture of Theta will emerge. It is traditionally supposed by readers and critics of Aristotle that the Metaphysics, especially books Zeta, Eta and Theta (the so-called 'Central Books'), is addressed to the question of what it is for something, anything, to be an ousia. On this view, Zeta is the 'heart' of the Metaphysics, and Eta and Theta are subordinate to it. More specifically, according to this view, after Aristotle has addressed the question of what it is for something, anything, to be an ousia in Zeta, what is left to be addressed in Eta and Theta are some issues that remain unresolved in Zeta.
Keywords: Social Sciences and Philosophy, Ph.D.; PhD Trinity College Dublin, 2017